A class of nonlinear stochastic volatility models and its implications on pricing currency options - YU, Jun (Institutional Knowledge at Singapore Management University, 2006)
A class of stochastic volatility (SV) models is proposed by applying the Box–Cox transformation to the volatility equation. This class of nonlinear SV (N-SV) models encompasses all standard SV models, including the well-known lognormal (LN) SV model. It allows to empirically compare and test all standard specifications in a very convenient way and provides a measure of the degree of departure from the classical models. A likelihood-based technique is developed for analyzing the model. Daily dollar/pound exchange rate data provide some evidence against LN model and strong evidence against all the other classical specifications. An efficient algorithm is proposed to study the economic importance of the proposed model on pricing currency options.